Religious tolerance in Islamic education: a systematic literature review - Yang Marya Abd Khahar; Jaffary Awang; Zaizul Ab. Rahman; Ahmad Munawar Ismail (Penerbit Universiti Kebangsaan Malaysia, 2025)
The rise of religious extremism underscores the critical role of Islamic education in fostering social harmony. This Systematic Literature Review (SLR) examines the diverse definitions, curricular integration, and pedagogical approaches to religious tolerance within Islamic education systems, as well as the challenges associated with their implementation. The review synthesises empirical studies, including content analysis, quasi-experimental designs, and qualitative case studies, from Kuwait, Indonesia, Malaysia, and Iran. Data were drawn from curricula, textbooks, and the perspectives of teachers and students to identify definitions, effective models and implementation barriers. Tolerance is broadly defined as mutual respect and the rejection of coercion. Levels of integration vary by national context: comprehensive in Kuwait, limited in Indonesia and hegemonic in Iran. Inclusive Islamic Education (PAI) materials and Qur’an-based pedagogical models in Indonesia have demonstrably enhanced student tolerance and reduced tendencies toward radicalism. Key challenges include high levels of student intolerance, curriculum weaknesses, state-imposed ideological constraints, intolerant social media narratives and narrow interpretations of religious texts. Promoting religious tolerance through Islamic education is a complex undertaking. Despite several practical innovations, systemic gaps, restrictive state policies, and external radical influences continue to hinder holistic implementation. Future initiatives require comprehensive strategies that are contextually sensitive, particularly in the interpretation of religious texts and awareness of sociopolitical realities, to achieve genuine inclusivity.